PENGEMBANGAN MEDIA PEMBELAJARAN BUSY BOOK UNTUK PERKEMBANGAN KEMAMPUAN BERHITUNG ANAK USIA 4-5 TAHUN - Rosalina, Citra Dewi; Agustina, Devya Titin; Apriliyana, Firdausi Nuzula (Program Studi PG PAUD Universitas PGRI Ronggolawe, 2024)
This type of research is development research that will produce Busy book learning media products. The purpose of this research is as a media for learning to count with the development of Busy Book media. as an alternative to learning visual media to recognize numbers and counting in children aged 4-5 years so that it can attract and motivate children to learn the development of numeracy skills of children aged 4-5 years. The research and development used is research and development (R&D). This study uses a development procedure from Borg and Gall. by using a level 1 testing model (examining without testing). With 5 research steps that can be mentioned, namely: one potential problem, two data collection, three product designs, and four design validations, finally the design is tested. The research site is at the PGRI Ronggolawe University Tuban with two techniques used in data collection, namely interview techniques and questionnaire techniques, two validations of material experts and media experts. With three media expert validators and three material expert validators. The research data were analyzed using descriptive and quantitative analysis techniques. The results of the data analysis obtained are an average score of 3.8 in the category of